Ancient social landscapes of northwestern Argentina: preliminary results of an integrated approach to obsidian and ceramic provenance - Lazzari, Marisa (2009)
This article presents the results of ongoing instrumental neutron activation analyses (INAA) conducted on archaeological artifacts from the Formative period of northwestern Argentina (NWA). These studies are part of a wider archaeological project that seeks to understand the structure of the social landscape of the period by examining domestic and burial evidence from a wide range of villages across the area known as the southern Calchaquí valleys. Elemental data is discussed in the light of its potential contribution to reassess past social interaction strategies in the region.